Method for directly regenerating anode material of waste lithium iron phosphate battery into lithium manganese iron phosphate by controlling lithium iron antisite defect
By designing a micro-lithium-rich lithium iron phosphate material, the problem of iron lithium in the positive electrode material of waste lithium iron phosphate battery is solved, and efficient material recycling and performance improvement is achieved, the process is environmentally friendly and operation is simple.
Patent Information
- Application Number
- CN202510095074.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The prior art is difficult to effectively recover and regenerate the positive electrode material of lithium iron phosphate battery, especially to reduce the problem of reverse position defects of lithium iron, which affects the conductivity and service life of the material.
By designing a micro-lithium-rich structure, the used lithium iron phosphate battery positive electrode material is ball milled and mixed to obtain a precursor of Li1.05Fe0.35Mn0.6PO4, and then pre-fired and calcined in an inert gas to form a lithium manganese iron phosphate material with reduced inversion defect of lithium iron phosphate.
It significantly improves the ion and electronic conductivity of lithium manganese iron phosphate material, improves the specific capacity and discharge voltage, reduces the reverse position defect of lithium iron, and has a simple process, environmentally friendly, safe and reliable process.
Smart Images

Figure CN119822352A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy materials, and in particular relates to a method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium manganese iron phosphate by controlling iron lithium antisite defects. Background Art
[0002] In the context of dual carbon, the large-scale popularization of electric vehicles and the rapid development of lithium-ion batteries will result in a large number of batteries that need to be retired in the future. The research on the recycling of retired lithium-ion batteries is currently focused on how to recover the valuable metals in them. There has been slow progress in direct regeneration. How to directly recycle retired batteries or recycle them at a high value is still a difficult problem.
[0003] Lithium iron phosphate (LiFePO4) belongs to the olivine structure and is an orthorhombic Pnma space group. Lithium iron phosphate batteries are common energy storage / power battery cathode materials. The material has inherent iron-lithium antisite defects (part of the iron atoms occupy the lithium site), which affects the transmission of lithium ions, resulting in reduced ion and electronic conductivity, affecting the use of materials. Retired lithium iron phosphate batteries lack lithium during long cycles, leading to the formation of phosphate phases, which are prone to more iron-lithium antisite defects, resulting in a decrease in specific capacity and a decrease in discharge voltage. How to recycle lithium iron phosphate cathode materials at a high value and reduce iron-lithium antisite defects during the recycling process has become the key and difficulty in the current recycling of lithium iron phosphate cathode materials. Summary of the invention
[0004] In order to solve the existing problems, the present invention designs a method for directly recycling waste lithium iron phosphate battery positive electrode materials into lithium iron manganese phosphate. Through the design of a special micro-lithium-rich structure, waste lithium iron phosphate battery positive electrode materials can be recycled into micro-lithium-rich lithium iron manganese phosphate, effectively reducing the iron-lithium anti-site defects in the lithium iron manganese phosphate, effectively improving the ion and electronic conductivity, and the capacity and discharge voltage of the recovered lithium iron manganese phosphate are significantly improved.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium manganese iron phosphate by controlling the anti-site defects of lithium iron, comprising the following steps:
[0007] (1) calcining the discarded lithium iron phosphate battery positive electrode sheet at 400° C. for 4 h under inert gas to remove the polymer binder and carbon coating, separating it from the current collector aluminum foil and grinding it to obtain the positive electrode material powder;
[0008] (2) dissolving the positive electrode material powder obtained in step (1) in aqua regia and performing microwave digestion, and measuring its chemical composition by ICP-OES method;
[0009] (3) mixing the positive electrode material powder obtained in step (1) with a lithium source, a manganese source, a phosphorus source and a carbon source in a slightly lithium-rich molar ratio by ball milling, and then drying to obtain a precursor powder;
[0010] (4) pre-calcining the precursor powder obtained in step (3) at 400° C. for 2 h under inert gas;
[0011] (5) The powder obtained in step (4) is calcined at 650-700° C. for 10 h under an inert gas to obtain a regenerated positive electrode powder material.
[0012] In step (3), the designed slightly lithium-rich molar stoichiometric ratio is Li:(Fe+Mn):P=(1.05-1.1):(0.9-0.95):1, and the molar stoichiometric ratio of iron to manganese is Fe:Mn=(0.3-0.35):0.6, wherein the extra lithium occupies the iron position.
[0013] Preferably, in step (3), the designed slightly lithium-rich molar ratio is Li:Fe:Mn:P=1.05:0.35:0.6:1, wherein the additional lithium occupies the iron position, and the chemical formula of the corresponding regenerated positive electrode powder material is Li 1.05 Fe 0.35 Mn 0.6 PO4.
[0014] The present invention designs a method for directly recycling lithium iron phosphate into lithium iron manganese phosphate. By simply adjusting the stoichiometric ratio, the lithium iron phosphate can be recycled into lithium iron manganese phosphate with any manganese-iron ratio, and the lithium iron anti-site defects in the lithium iron manganese phosphate can be reduced by adjusting the lithium-iron ratio, thereby effectively improving the ionic and electronic conductivity, specific capacity and discharge voltage.
[0015] The inert gas is one of argon and nitrogen.
[0016] In step (2), the aqua regia is a mixture of concentrated hydrochloric acid and concentrated nitric acid in a volume ratio of 3:1.
[0017] In step (3), the lithium source may be a lithium-containing substance used in the art for preparing lithium iron manganese phosphate, and may be at least one of lithium carbonate, lithium acetate, lithium oxalate, lithium oxide, and lithium hydroxide.
[0018] Preferably, the lithium source is lithium acetate and / or lithium dihydrogen phosphate.
[0019] In step (3), the manganese source may be a manganese-containing substance used in the art for preparing lithium manganese iron phosphate, and may be selected from at least one of manganese carbonate, manganese oxalate, manganese acetate, manganese oxide, manganese trioxide, and manganese tetraoxide. Preferably, the manganese source is manganese oxalate.
[0020] In step (3), the phosphorus source may be a phosphorus-containing substance used in the art for preparing lithium manganese iron phosphate, and may be at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium dihydrogen phosphate. Preferably, the phosphorus source is lithium dihydrogen phosphate.
[0021] In step (3), the carbon source can be a carbon-containing substance used in the art for preparing carbon-coated lithium manganese iron phosphate, and can be selected from at least one of starch, sucrose, glucose, cellulose, polyvinyl alcohol, polyethylene glycol, sodium carboxymethyl cellulose, citric acid, lactic acid, and succinic acid. Preferably, the carbon source is sucrose.
[0022] Compared with the prior art, the advantages of the present invention are:
[0023] 1. The method of the present invention directly regenerates waste lithium iron phosphate battery positive electrode materials into lithium iron manganese phosphate, which can control the anti-site defects of lithium iron phosphate and design a material different from the currently commonly used lithium iron manganese phosphate material (chemical composition is Li 1.0 Fe 0.4 Mn 0.6 PO4) (micro-lithium-rich structure, chemical composition is Li 1.05 Fe 0.35 Mn 0.6 PO4, in which part of the extra lithium occupies the iron position, and the formation energy of the anti-site defect of iron-lithium is increased to achieve the purpose of reducing the anti-site defect of iron-lithium), the lithium source, phosphorus source, manganese source and carbon source are mixed and ball-milled to obtain a lithium iron phosphate precursor with a slightly lithium-rich structure, and then pre-burned at 400 degrees for 2 hours under inert gas and calcined at 650 degrees for 10 hours to obtain the lithium iron phosphate with a slightly lithium-rich structure. The lithium iron phosphate prepared by this method can be used as a positive electrode material for lithium-ion batteries. Compared with waste lithium iron phosphate, it has a significant improvement in specific capacity and median voltage. The recovery method is simple to operate, does not use any solvent, and the entire process is green, environmentally friendly, safe and reliable.
[0024] 2. This invention is the first to design a slightly lithium-rich structure, which is different from the traditional lithium iron manganese phosphate material. The chemical composition of this structure is Li 1.05 Fe 0.35 Mn 0.6 PO4, in which part of the additional lithium occupies the iron site. This structure significantly increases the formation energy of the iron-lithium antisite defect and can effectively reduce the iron-lithium antisite defect.
[0025] 3. The present invention is different from the prior art in that waste lithium iron phosphate is leached for metal recovery, and the waste lithium iron phosphate is directly regenerated as a raw material into lithium iron manganese phosphate material without changing the lattice structure of the waste lithium iron phosphate.
[0026] 4. The process flow of the present invention is simple, does not use any organic solvent, is basically free of environmental pollution, and has high industrial operability.
[0027] 5. The lithium manganese iron phosphate material of the present invention has the advantages of high ion and electronic conductivity, specific capacity and discharge voltage, and excellent cycle stability, and is suitable for promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The X-ray diffraction pattern of the lithium manganese iron phosphate material obtained in Example 1 of the present invention is
[0029] Figure 2 The X-ray diffraction pattern of the lithium manganese iron phosphate material obtained in Example 2 of the present invention is
[0030] Figure 3 The X-ray diffraction pattern of the lithium manganese iron phosphate material obtained in Example 3 of the present invention is
[0031] Figure 4 The X-ray diffraction pattern of the lithium manganese iron phosphate material obtained in Comparative Example 1 of the present invention is
[0032] Figure 5 The X-ray diffraction patterns of the lithium manganese iron phosphate materials obtained in Examples 1 and 2 of the present invention and their local magnified images are shown.
[0033] Figure 6 This is a spectrum obtained by refining and fitting the X-ray diffraction spectrum of the lithium manganese iron phosphate material obtained in Example 1 of the present invention through the Retrieve method.
[0034] Figure 7 This is a spectrum obtained by refining and fitting the X-ray diffraction spectrum of the lithium manganese iron phosphate material obtained in Comparative Example 1 of the present invention through the Retrieve method.
[0035] Figure 8 Solid NMR of the lithium manganese iron phosphate material obtained in Example 1 of the present invention and Comparative Example 1 7 Spectrum obtained from Li spectrum test.
[0036] Fig. 9 This is a specific capacity / voltage curve obtained by assembling a half-cell of the lithium manganese iron phosphate material obtained in Example 1 of the present invention.
[0037] Fig.10 This is a specific capacity / voltage curve obtained by assembling a half-cell of the lithium manganese iron phosphate material obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0038] For the convenience of understanding the present invention, the present invention will be described more comprehensively and meticulously in conjunction with the accompanying drawings and preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those skilled in the art generally understand. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.
[0039] The above scheme is further described below in conjunction with specific implementation examples, and the preferred embodiments of the present invention are described in detail as follows:
[0040] Embodiment 1:
[0041] In this embodiment, a method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium manganese iron phosphate by controlling the antisite defects of lithium iron phosphate mainly includes the following steps:
[0042] (1) The discarded lithium iron phosphate positive electrode sheet is calcined at 400° C. for 4 h under an inert gas to remove the polymer binder and the carbon coating, and then separated from the current collector aluminum foil and ground to obtain a positive electrode material powder; the inert gas is argon.
[0043] (2) Weigh 0.0601 g of the positive electrode material powder obtained in step (1), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times and obtain its chemical composition by ICP-OES method, which is about Li:Fe:P=0.83:1:1;
[0044] (3) Weigh 2.10 g of the positive electrode material powder obtained in step (1), 3.58 g of manganese oxalate dihydrate, 2.06 g of lithium dihydrogen phosphate, 0.260 g of lithium acetate, 0.640 g of sucrose, 40.0 g of agate milling beads with a diameter of 6 mm, and 20.0 g of agate milling beads with a diameter of 10 mm, add 10 ml of anhydrous ethanol as a dispersant, and grind on a planetary ball mill at 600 r min -1 The precursor powder was obtained by ball milling at a speed of 8000 g for 8 h and then drying;
[0045] (4) Place the precursor powder in a tube furnace and heat at 3 °C min under an argon atmosphere. -1 The temperature was raised to 400 °C at a rate of 100 °C and maintained for 2 h;
[0046] (5) The powder obtained in step (4) was placed in a tube furnace and heated at 3 °C min under an argon atmosphere. -1 The temperature was raised to 650°C at a heating rate and maintained for 10 h. After cooling, about 3 g of regenerated positive electrode powder material was obtained.
[0047] (6) Weigh 0.0601 g of the positive electrode material powder obtained in step (5), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times, and obtain its chemical composition by ICP-OES method, which is about Li:Fe:Mn:P=1.05:0.35:0.6:1, that is, the chemical formula of the obtained positive electrode powder material is Li 1.05 Fe 0.35 Mn 0.6 PO4.
[0048] Embodiment 2:
[0049] In this embodiment, a method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium manganese iron phosphate by controlling the antisite defects of lithium iron phosphate mainly includes the following steps:
[0050] (1) The discarded lithium iron phosphate positive electrode sheet is calcined at 400° C. for 4 h under an inert gas to remove the polymer binder and the carbon coating, and then separated from the current collector aluminum foil and ground to obtain a positive electrode material powder; the inert gas is argon.
[0051] (2) Weigh 0.0601 g of the positive electrode material powder obtained in step (1), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times and obtain its chemical composition by ICP-OES method, which is about Li:Fe:P=0.83:1:1;
[0052] (3) Weigh 2.10 g of the positive electrode material powder obtained in step (1), 3.58 g of manganese oxalate dihydrate, 2.06 g of lithium dihydrogen phosphate, 0.260 g of lithium acetate, 0.640 g of sucrose, 40.0 g of agate milling beads with a diameter of 6 mm, and 20.0 g of agate milling beads with a diameter of 10 mm, add 10 ml of anhydrous ethanol as a dispersant, and grind on a planetary ball mill at 600 r min -1 The precursor powder was obtained by ball milling at a speed of 8000 g for 8 h and then drying;
[0053] (4) Place the precursor powder in a tube furnace and heat at 3 °C min under an argon atmosphere. -1 The temperature was raised to 400 °C at a rate of 100 °C and maintained for 2 h;
[0054] (5) The powder obtained in step (4) was placed in a tube furnace and heated at 3 °C min under an argon atmosphere. -1 The temperature was raised to 700°C at a heating rate and maintained for 10 h. After cooling, about 3 g of regenerated positive electrode powder material was obtained.
[0055] (6) Weigh 0.0601 g of the positive electrode material powder obtained in step (5), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times, and obtain its chemical composition by ICP-OES method, which is about Li:Fe:Mn:P=1.05:0.35:0.6:1, that is, the chemical formula of the obtained positive electrode powder material is Li 1.05 Fe 0.35 Mn 0.6 PO4.
[0056] Embodiment 3:
[0057] In this embodiment, a method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium manganese iron phosphate by controlling the antisite defects of lithium iron phosphate mainly includes the following steps:
[0058] (1) The discarded lithium iron phosphate positive electrode sheet is calcined at 400° C. for 4 h under an inert gas to remove the polymer binder and the carbon coating, and then separated from the current collector aluminum foil and ground to obtain a positive electrode material powder; the inert gas is argon.
[0059] (2) Weigh 0.0601 g of the positive electrode material powder obtained in step (1), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times and obtain its chemical composition by ICP-OES method, which is about Li:Fe:P=0.83:1:1;
[0060] (3) Weigh 1.57 g of the positive electrode material powder obtained in step (1), 3.56 g of manganese oxalate dihydrate, 2.54 g of lithium dihydrogen phosphate, 0.33 g of lithium acetate, 0.642 g of sucrose, 40.0 g of agate milling beads with a diameter of 6 mm, and 20.0 g of agate milling beads with a diameter of 10 mm, add 10 ml of anhydrous ethanol as a dispersant, and grind on a planetary ball mill at 600 r min -1 The precursor powder was obtained by ball milling at a speed of 8000 g for 8 h and then drying;
[0061] (4) Place the precursor powder in a tube furnace and heat at 3 °C min under an argon atmosphere. -1 The temperature was raised to 400 °C at a rate of 100 °C and maintained for 2 h;
[0062] (5) The powder obtained in step (4) was placed in a tube furnace and heated at 3 °C min under an argon atmosphere. -1 The temperature was raised to 650°C at a heating rate and maintained for 10 h. After cooling, about 5 g of regenerated positive electrode powder material was obtained.
[0063] (6) Weigh 0.0601 g of the positive electrode material powder obtained in step (5), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times, and obtain its chemical composition by ICP-OES method, which is about Li:Fe:Mn:P=1.1:0.3:0.6:1, that is, the chemical formula of the obtained positive electrode powder material is Li 1.1 Fe 0.3 Mn 0.6 PO4.
[0064] Embodiment 4:
[0065] In this embodiment, a method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium manganese iron phosphate by controlling the antisite defects of lithium iron phosphate mainly includes the following steps:
[0066] (1) The discarded lithium iron phosphate positive electrode sheet is calcined at 400° C. for 4 h under an inert gas to remove the polymer binder and the carbon coating, and then separated from the current collector aluminum foil and ground to obtain a positive electrode material powder; the inert gas is argon.
[0067] (2) Weigh 0.0601 g of the positive electrode material powder obtained in step (1), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times and obtain its chemical composition by ICP-OES method, which is about Li:Fe:P=0.83:1:1;
[0068] (3) Weigh 1.57 g of the positive electrode material powder obtained in step (1), 3.56 g of manganese oxalate dihydrate, 2.54 g of lithium dihydrogen phosphate, 0.33 g of lithium acetate, 0.642 g of sucrose, 40.0 g of agate milling beads with a diameter of 6 mm, and 20.0 g of agate milling beads with a diameter of 10 mm, add 10 ml of anhydrous ethanol as a dispersant, and grind on a planetary ball mill at 600 r min -1 The precursor powder was obtained by ball milling at a speed of 8000 g for 8 h and then drying;
[0069] (4) Place the precursor powder in a tube furnace and heat at 3 °C min under an argon atmosphere. -1 The temperature was raised to 400 °C at a rate of 100 °C and maintained for 2 h;
[0070] (5) The powder obtained in step (4) was placed in a tube furnace and heated at 3 °C min under an argon atmosphere. -1 The temperature was raised to 700°C at a heating rate and maintained for 10 h, and about 5 g of regenerated positive electrode powder material was obtained after cooling;
[0071] (6) Weigh 0.0601 g of the positive electrode material powder obtained in step (5), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times, and obtain its chemical composition by ICP-OES method, which is about Li:Fe:Mn:P=1.1:0.3:0.6:1, that is, the chemical formula of the obtained positive electrode powder material is Li 1.1 Fe 0.3 Mn 0.6 PO4. Comparative Example 1:
[0072] In this embodiment, a method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium manganese iron phosphate mainly includes the following steps:
[0073] (1) calcining the discarded lithium iron phosphate positive electrode sheet at 400° C. for 4 h under an inert gas to remove the polymer binder and the carbon coating, separating the waste lithium iron phosphate positive electrode sheet from the current collector aluminum foil and grinding the waste lithium iron phosphate positive electrode sheet to obtain a positive electrode material powder; the inert gas is argon or nitrogen.
[0074] (2) Weigh 0.0601 g of the positive electrode material powder obtained in step (1), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times and obtain its chemical composition by ICP-OES method, which is about Li:Fe:P=0.83:1:1;
[0075] (3) Weigh 1.57 g of the positive electrode material powder obtained in step (1), 2.68 g of manganese oxalate dihydrate, 1.64 g of lithium dihydrogen phosphate, 0.110 g of lithium acetate, 0.480 g of sucrose, 40.0 g of agate milling beads with a diameter of 6 mm, and 20.0 g of agate milling beads with a diameter of 10 mm, add 10 ml of anhydrous ethanol as a dispersant, and grind on a planetary ball mill at 600 r min -1 The precursor powder was obtained by ball milling at a speed of 8000 g for 8 h and then drying;
[0076] (4) Place the precursor powder in a tube furnace and heat at 3 °C min under an argon atmosphere. -1 The temperature was raised to 400 °C at a rate of 100 °C and maintained for 2 h;
[0077] (5) The powder obtained in step (4) was placed in a tube furnace and heated at 3 °C min under an argon atmosphere. -1 The temperature was raised to 650°C at a heating rate and maintained for 10 h. After cooling, about 4 g of regenerated positive electrode powder material was obtained.
[0078] (6) Weigh 0.0601 g of the positive electrode material powder obtained in step (5), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times, and obtain its chemical composition by ICP-OES method, which is about Li:Fe:Mn:P=1.0:0.4:0.6:1, that is, the chemical formula of the obtained positive electrode powder material is Li 1.0 Fe0.4 Mn 0.6 PO4. Comparative Example 2:
[0079] In this embodiment, a method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium manganese iron phosphate mainly includes the following steps:
[0080] (1) calcining the discarded lithium iron phosphate positive electrode sheet at 400° C. for 4 h under an inert gas to remove the polymer binder and the carbon coating, separating the waste lithium iron phosphate positive electrode sheet from the current collector aluminum foil and grinding the waste lithium iron phosphate positive electrode sheet to obtain a positive electrode material powder; the inert gas is argon or nitrogen.
[0081] (2) Weigh 0.0601 g of the positive electrode material powder obtained in step (1), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times and obtain its chemical composition by ICP-OES method, which is about Li:Fe:P=0.83:1:1;
[0082] (3) Weigh 1.57 g of the positive electrode material powder obtained in step (1), 2.68 g of manganese oxalate dihydrate, 1.64 g of lithium dihydrogen phosphate, 0.110 g of lithium acetate, 0.480 g of sucrose, 40.0 g of agate milling beads with a diameter of 6 mm, and 20.0 g of agate milling beads with a diameter of 10 mm, add 10 ml of anhydrous ethanol as a dispersant, and grind on a planetary ball mill at 600 r min -1 The precursor powder was obtained by ball milling at a speed of 8000 g for 8 h and then drying;
[0083] (4) Place the precursor powder in a tube furnace and heat at 3 °C min under an argon atmosphere. -1 The temperature was raised to 400 °C at a rate of 100 °C and maintained for 2 h;
[0084] (5) The powder obtained in step (4) was placed in a tube furnace and heated at 3 °C min under an argon atmosphere. -1 The temperature was raised to 650°C at a heating rate and maintained for 10 h. After cooling, about 4 g of regenerated positive electrode powder material was obtained.
[0085] (6) Weigh 0.0601 g of the positive electrode material powder obtained in step (5), add 2 ml of aqua regia and digest it by microwave, adjust the volume to 25 ml, dilute it 100 times, and obtain its chemical composition by ICP-OES method, which is about Li:Fe:Mn:P=1.0:0.4:0.6:1, that is, the chemical formula of the obtained positive electrode powder material is Li 1.0 Fe 0.4 Mn 0.6 PO4.
[0086] Performance test experiment
[0087] The equipment used in the performance test experiments, embodiments and comparative examples of the present invention are shown in Appendix 1:
[0088] Table 1
[0089]
[0090] Specific test method:
[0091] The lithium manganese iron phosphate positive electrode material powder (Li 1.05 Fe 0.35 Mn 0.6 PO4、Li 1.1 Fe 0.3 Mn 0.6 PO4、Li 1.0 Fe 0.4 Mn 0.6 PO4) were ground and analyzed on a German Bruker D8 X-ray diffractometer at 1°min -1 The test results are as follows: Figure 1 , 2 , 3, and 4. The enlarged diagram comparing Example 1 and Example 2 is shown in Figure 5 The X-ray diffraction patterns of the lithium manganese iron phosphate materials obtained in Example 1 and Comparative Example 1 were refined and fitted by the Retrieve method and the patterns were shown as follows: Figure 6 , 7 The unit cell parameters obtained by refining and fitting the X-ray diffraction patterns of the lithium manganese iron phosphate materials obtained in Example 1 and Comparative Example 1 are shown in Table 2 and Table 3.
[0092] Table 2
[0093]
[0094] Table 3
[0095]
[0096] The lithium manganese iron phosphate positive electrode material (Li 1.05 Fe 0.35 Mn 0.6 PO4、Li 1.0 Fe 0.4 Mn 0.6 PO4) were respectively subjected to solid state nuclear magnetic resonance spectrometry (magnetic field strength 14.1T). 7 Li dipole decoupling magic angle spinning (DD / MAS) experiment, such as Figure 8 The instrument 7The Li Larmor frequency was 233.08 MHz, and proton decoupling (TPPM) was performed during the acquisition. The powder sample was placed in a 4.0 mm pencil-type zirconia rotor. The spectrum was acquired at a rotation speed of 8 kHz with a 3 s recycle delay, approximately 90 degree pulses (3.8 us), and 128 scans. The Li signal of LiCl was used as 7 Reference for Li chemical shift.
[0097] The lithium manganese iron phosphate positive electrode material (Li 1.05 Fe 0.35 Mn 0.6 PO4、Li 1.1 Fe 0.3 Mn 0.6 PO4、Li 1.0 Fe 0.4 Mn 0.6 PO4) was mixed with polyvinylidene fluoride binder and carbon black conductive agent in a mass ratio of 8:1:1 to obtain a corresponding mixture, and the mixture was added to NMP (N-methylpyrrolidone) solvent to obtain a mixed slurry, and then each mixed slurry was coated on the surface of the aluminum substrate, and the corresponding positive electrode sheet was obtained after drying, and the drying temperature was 120°C. The obtained positive electrode sheet and lithium sheet were used as the positive and negative electrodes of the battery, and the button half-cell was assembled using Celgard 2500 battery separator, LB-878 electrolyte, and CR2032 battery shell.
[0098] The half-cell was tested using a Land CT 2001A blue battery tester at a rate of 0.2C / 1C (1C = 170 mAh g -1 ) conditions, the charge and discharge test is carried out, and the test results are as follows Fig. 9 , 10 (Specific capacity / voltage curve obtained by assembling half-cells of lithium manganese iron phosphate materials obtained in Example 1 and Comparative Example 1) and as shown in Table 4.
[0099] The charge and discharge capacity and coulombic efficiency of the lithium manganese iron phosphate materials obtained in Examples 1-4 and Comparative Examples 1-2 are shown in Table 4.
[0100] Table 4
[0101]
[0102] Test result analysis:
[0103] (1) By Figure 1 , 2, 3, and 4 show that the positive electrode materials prepared in Examples 1, 2, 3 and Comparative Example 1 are compared with the lithium iron phosphate standard card, and their characteristic peaks correspond one to one, and all of them move to a small angle due to the addition of manganese, indicating that lithium manganese iron phosphate positive electrode materials are prepared. The XRD characteristic peaks are sharp, indicating good crystallinity. The ratio of the (020) peak to the (111) peak in Example 1 is 1.019, which is slightly larger than 0.955 in Comparative Example 1, indicating that it is a slightly lithium-rich structure. There is a mixed phase Li3PO4 in Example 3, indicating that the lithium content in the slightly lithium-rich structure should be less than 1.1, otherwise impurities will be generated.
[0104] (2) By Figure 5 It can be seen that the slightly lithium-rich structure in Example 1 can only be formed below 650° C., and the slightly lithium-rich structure is destroyed at 700° C. and partially converted into a lithium phosphate structure.
[0105] (3) By Figure 6 , 7 As shown in Tables 2 and 3, the positive electrode material prepared in Example 1 has a slightly lithium-rich structure, in which part of the lithium occupies the iron site and there are fewer anti-site defects, which is one of the reasons for the excellent performance of the material.
[0106] (4) By Figure 8 It can be seen that the positive electrode material prepared in Example 1 has two lithiums in different chemical environments, which fully demonstrates that it is a slightly lithium-rich structure, which is different from the conventional lithium iron manganese phosphate material (i.e., Comparative Example 1).
[0107] (5) By Fig. 9 , 10 It can be seen that the positive electrode material prepared in Example 1 has a discharge capacity of about 155 mAh g at a rate of 0.2C. -1 The discharge capacity at 1C rate is about 137 mAh g -1 The 1C discharge medium voltage is about 3.73V, which is better than that of comparative example 1, indicating that the material has a high capacity and excellent rate performance.
[0108] (6) As shown in Table 4, the discharge specific capacity and first cycle coulombic efficiency of the positive electrode material prepared in Example 1 at a rate of 0.2C are better than those of other examples and comparative examples. The material prepared in Example 2 is heated at 700 degrees, and the slightly lithium-rich structure is destroyed, resulting in the generation of lithium phosphate, which leads to a decrease in discharge specific capacity and coulombic efficiency. The material prepared in Example 3 has a decrease in redox couple due to the reduction of iron in the stoichiometric ratio, resulting in a decrease in specific capacity. The reason for the decrease in specific capacity in Example 4 is the same as that in Example 2. Comparative Examples 1 and 2 have lower specific capacities due to the high iron-lithium anti-site defects.
[0109] In summary, the present invention is a method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium iron manganese phosphate. The operation is simple and convenient, no solvent is used, basically pollution-free, and practical. It can be quickly promoted to industrial production and has important practical significance in the field of recycling of waste batteries.
Claims
1. A method for directly regenerating waste lithium iron phosphate battery positive electrode materials into lithium manganese iron phosphate by controlling the anti-site defects of lithium iron, characterized in that: It includes the following steps: (1) calcining the discarded lithium iron phosphate battery positive electrode sheet at 400° C. for 4 h under inert gas to remove the polymer binder and carbon coating, separating it from the current collector aluminum foil and grinding it to obtain the positive electrode material powder; (2) dissolving the positive electrode material powder obtained in step (1) in aqua regia and performing microwave digestion, and measuring its chemical composition by ICP-OES method; (3) mixing the positive electrode material powder obtained in step (1) with a lithium source, a manganese source, a phosphorus source and a carbon source in a slightly lithium-rich molar ratio by ball milling, and then drying to obtain a precursor powder; (4) pre-calcining the precursor powder obtained in step (3) at 400° C. for 2 h under inert gas; (5) The powder obtained in step (4) is calcined at 650-700° C. for 10 h under an inert gas to obtain a regenerated positive electrode powder material.
2. The method according to claim 1, characterized in that: In step (3), the designed slightly lithium-rich molar stoichiometric ratio is Li:(Fe+Mn):P=(1.05-1.1):(0.9-0.95):1, wherein the molar stoichiometric ratio of iron to manganese is Fe:Mn=(0.3-0.35):0.6, wherein the extra lithium occupies the iron position.
3. The method according to claim 2, characterized in that: In step (3), the designed slightly lithium-rich molar ratio is Li:Fe:Mn:P=1.05:0.35:0.6:1, wherein the additional lithium occupies the iron position, and the chemical formula of the resulting regenerated positive electrode powder material is Li 1.05 Fe 0.35 Mn 0.6 PO4.
4. The method according to claim 1, characterized in that: The inert gas is one of argon and nitrogen.
5. The method according to claim 1, characterized in that: In step (2), the aqua regia is a mixture of concentrated hydrochloric acid and concentrated nitric acid in a volume ratio of 3:
1.
6. The method according to claim 1, characterized in that: In step (3), the lithium source is at least one of lithium carbonate, lithium acetate, lithium oxalate, lithium oxide, and lithium hydroxide.
7. The method according to claim 1, characterized in that: In step (3), the manganese source is at least one of manganese carbonate, manganese oxalate, manganese acetate, manganese oxide, dimanganese trioxide, and trimanganese tetraoxide.
8. The method according to claim 1, characterized in that: In step (3), the phosphorus source is at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium dihydrogen phosphate.
9. The method according to claim 1, characterized in that: In step (3), the carbon source is at least one of starch, sucrose, glucose, cellulose, polyvinyl alcohol, polyethylene glycol, sodium carboxymethyl cellulose, citric acid, lactic acid, and succinic acid.
10. A positive electrode powder material prepared by the method according to claim 3, characterized in that: It is directly regenerated from waste lithium iron phosphate battery positive electrode materials, and its chemical formula is Li 1.05 Fe 0.35 Mn 0.6 PO4.
Citation Information
Patent Citations
Non-stoichiometric lithium iron manganese phosphate positive electrode material as well as preparation method and application thereof
CN113161523A
Method for recycling waste phosphate positive electrode material
CN114583313A
Method for repairing and regenerating lithium iron manganese phosphate by using lithium iron phosphate waste powder and lithium iron manganese phosphate waste powder
CN116621146A
Method for quickly upgrading and regenerating lithium iron manganese phosphate from lithium iron phosphate waste powder
CN119284856A
Method of preparing battery electrodes
US20170207441A1